Lower Arm Muscle Activation during Indirect-Localized Vibration: The Influence of Skill Levels When Applying Different Acceleration Loads - Padulo, Johnny; Di Giminiani, Riccardo; Dello Iacono, Antonio; Zagatto, Alessandro M.; Migliaccio, Gian M.; Grgantov, Zoran; Ardigò, Luca P. (Frontiers in Physiology, 2016)
We investigated the electromyographic response to synchronous indirect-localized vibration interventions in international and national table tennis players. Twenty-six male table tennis players, in a standing position, underwent firstly an upper arms maximal voluntary contraction and thereafter two different 30-s vibration interventions in random order: high acceleration load (peak acceleration=12.8 g, frequency=40 Hz; peak-to-peak displacement=4.0 mm), and low acceleration load (peak acceleration=7.2 g, frequency=30 Hz, peak-to-peak displacement=4.0 mm). Surface electromyography root mean square from brachioradialis, extensor digitorum, flexor carpi radialis, and flexor digitorum superficialis recorded during the two vibration interventions was normalized to the maximal voluntary contraction recording. Normalized surface electromyography root mean square was higher in international table tennis players with respect to national ones in all the interactions between muscles and vibration conditions (P<0.05), with the exception of flexor carpi radialis (at low acceleration load, P>0.05). The difference in normalized surface electromyography root mean square between international table tennis players and national ones increased in all the muscles with high acceleration load (P<0.05), with the exception of flexor digitorum superficialis (P>0.05). The muscle activation during indirect-localized vibration seems to be both skill level and muscle dependent. These results can optimize the training intervention in table tennis players when applying indirect-localized vibration to lower arm muscles. Future investigations should discriminate between middle- and long-term adaptations in response to specific vibration loads.